ji Bioaktivitas Senyawa Glikosida dari Biji Keben (Barringtonia asiatica L. Kurz) - Bustanussalam, Bustanussalam; Simanjuntak, Partomuan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
The fruits or seeds of Keben (Barringtonia asiatica L. Kurz) were used traditionally for fish poisons, to curvestomach and headeach. The aim of this research was to isolate and identify bioactive compound of n-butanolfraction of active compound against Artemia salina Leach larvae. Isolation and purification of n-butanol fractionwere carried out by column chomatography (SiO2, CHCl3-MeOH) and high pressure liquid chromatography (RP,MeOH). The result of purification was than tested using BSLT methode. The test showed that, BABU-2.4 had thehighest activity with LC 50 value was 30.19 ppm. BABU-2.4 was identified with FT-IR spectrophotometer and NMR(proton and carbon) spectrophotometer as derivate of glicoside.